Ordbøker over norske bygdemål frå før 1814 - Vikør, Lars S. (LexicoNordica, 2000)
Before 1814, Norway was part of the Danish realm, and the written standard language was Danish, while the spoken dialects were Norwegian, derived from Old Norse and very different from Danish, not least in the vocabulary. There were published four Norwegian dialect dictionaries before 1814 (in 1646, 1749, 1780 and 1802), most of them by clergymen who wanted to aid their Danish-speaking colleagues in their understanding of local speech. They are discussed and compared in this article together with two unpublished 18th century manuscripts which in size and quality deserve the name “dictionaries” (they have been published in the 20th century). All these dictionaries are “pre-scientific”, but a development is discernible from a more encyclopedic type to a more purely lexicographic type. This may have to do with a genre differentiation resulting from the development of more specialized works on different aspects of Norwegian nature and society.